Stališča študentov likovne pedagogike do pridobljenih splošnih in predmetno specifičnih kompetenc - Batič, Janja; Herzog, Jerneja; Duh, Matjaž (Revija za elementarno izobraževanje, 2009)
Motivating future art teachers to creatively plan and carry out lessons in art. During the study of art education, university students should gain general and subject-specific competences for teaching visual arts at the elementary or secondary school levels. As for subject-specific competences, the students should acquire these in the so-called technical subjects - drawing, painting, sculpture, graphics etc. In other words, these are the subjects that should help future art teachers to acquire - through their own artistic expression - specific information about various art forms, the expressive possibilities of art techniques, and a familiarization with different materials and tools. Unfortunately, it is often the case in art didactics classes, that students' have a rather poor knowledge of the fundamentals of art, which makes it difficult to achieve proper preparation for teaching. The harsh reality is that teachers lack motivation to deliver an in-depth presentation of expert subject matter, which is considered a basic element in the study of art education. During the 2008/2009 school year we conducted research that included students who were attending the third and fourth years of an Art Education program at the Faculty of Education in Maribor (n = 45). The data was obtained via a questionnaire. Our aim was to discover how students perceive the competences they have to acquire during their studies. The results clearly show that students are aware of the above-mentioned issues. According to them, the biggest problem is inadequate knowledge of specific art techniques and their expressive possibilities. As far as art forms are concerned, the most prominent issue appeared to be a poor knowledge of spatial(architectural) design.